Decrease Rate of the Renal Diameter in Chronic Hemodialysis Patients. (22nd May 2013) - Aoyagi, Teiichiro; Tachibana, Masaaki; Naganuma, Shinji
Abstract : We here present the results of ultrasonographic (US) evaluations on the alteration of renal diameter of chronic HD patients. Of 109 outpatient HD patients who had neither severe acquired cystic disease of the kidney nor hereditary polycystic kidney disease, we performed US two or three times to measure their maximum renal diameter (mean of both kidneys), and the yearly alteration rate was calculated. The average interval of the two measurements was 35.9 months, and the average HD duration from the HD induction to the first measurement was 29.5 months. The average decrease rate of renal diameter was4.34 ± 0.4 (SE) mm/year. No statistical difference was seen on the decrease rate in relation to gender, age and original disease (among three groups, glomerulonephritis and IgA nephropathy, diabetes, and others including hypertension). However, the decrease rate was large when the first measurement was close to the induction of hemodialysis, suggesting that the alteration rate reduced according to the hemodialysis vintage (5.3 ± 0.8  mm/year, first measurement not more than 10 months after induction of HD and1.5 ± 1.6  mm/year, first measurement more than 80 months after induction of HD). Renal diameter decreased approximately 4.3 mm each year, and the decrease rate slowed as the length of time on dialysis increased.